Anticancer effectiveness of Artemisia annua ethanol extract against MDAMB-231 cancer cells - Agustina, Rita; Ari, Psn Masruri Sulistiyanto; Sadikin, Nadya Audina N (Stem Cell and Cancer Research (SCCR), 2025)
Background: Breast cancer remains one of the leading causes of cancer deaths worldwide, with triple-negative breast cancer (TNBC) posing a significant therapeutic challenge due to its lack of hormonal receptors and resistance to conventional treatment. Artemisia annua L., a medicinal plant traditionally used in Chinese medicine, has received attention for its diverse bioactive compounds, including flavonoids, phenolic acids, and sesquiterpene lactones, which exhibit potential anticancer properties. This study aims to evaluate the in vitro cytotoxic effect of A. annua ethanol extract against MDA-MB-231 human breast cancer cells using the MTT assay. Methods: Extracts were prepared in 10% DMSO and tested at concentrations ranging from 0 to 1000 µg/mL. MDA-MB-231 cells were seeded in 96-well plates and incubated for 24 h before treatment. Post-treatment, cell viability was assessed via MTT assay, and absorbance was measured at 595 nm. The percentage of cytotoxicity was calculated, and the IC₅₀ value was determined through linear regression analysis. Results: The results showed a clear cytotoxic response depending on the dose, with the extract achieving an IC₅₀ value of 56.83 µg·mL-¹ indicating a fairly strong correlation between concentration and cytotoxicity. These findings indicate that A. annua contains bioactive compounds that are able to inhibit cancer cell proliferation. Conclusion: In conclusion, Artemisia annua ethanol extract showed moderate cytotoxic activity against MDA-MB-231 cells, supporting its potential as a complementary therapeutic agent for TNBC. Further studies are needed to elucidate its molecular mechanisms and evaluate its efficacy in vivo.